Scientific and organizational activity of historians for the preparation of the five-volume work «Histories of the Belarusian SSR» - Belazarovich, Viktor A. (Journal of the Belarusian State University. History, 2021)
The article analyses the process of creating a generalizing multi-volume work on the history of the Belarusian SSR. The publication reveals a unique experience of coordinating historical research related to the most important phenomena of the socio-political, socio-economic and cultural life of Belarus in the post-war period of the development of national historical science. For the first time in historiography, the scientific and organizational activity of creating a fundamental work reflecting the history of Belarus from ancient times to the mid 1970s has been studied. The idea of subordinating historical science to the interests of party politics is presented. The article is based on unpublished archival sources of the Central Scientific Archive of the National Academy of Sciences of Belarus, of the National Archives of the Republic of Belarus, which are being introduced into scientific circulation for the first time.
Keywords: history; historical science of Belarus; historiography of Belarus; Institute of History of the Academy of Sciences of the Belarusian SSR; history of the BSSR